FAKTOR-FAKTOR YANG MEMPENGARUHI PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK - Rahayu, Ruci Arizanda; Novitasari, Vivy; Maryanti, Eny (Jurnal Riset Mahasiswa Akuntansi, 2023)
The purpose of this study was to determine whether financial rewards, professional training, social values, work environment and labor market considerations influence accounting students at UMSIDA and UBHARA in choosing a career as a public accountant. The population or subjects in this study consisted of students of accounting study programs at Muhammadiyah Sidoarjo University and Bhayangkara University Surabaya class 2018. In this study, quantitative methods were used by distributing online questionnaires to accounting students at UMSIDA and UBHARA. Obtained as many as 80 respondents using the Slovin formula in sampling in this study. Partially, the results provide evidence that professional training and work environment influence career choices as public accountants by accounting students of UMSIDA and PBARA. On the other hand, financial rewards, social values, and labor market considerations cannot influence career choices as public accountants by accounting students of UMSIDA and UBARA